2020
DOI: 10.1155/2020/5197201
|View full text |Cite
|
Sign up to set email alerts
|

Association of Symptoms with Eating Habits and Food Preferences in Chronic Gastritis Patients: A Cross‐Sectional Study

Abstract: Purpose. There is a lack of research on the relationship between symptoms and dietary factors of chronic gastritis (CG) patients, and the contribution of dietary management in relieving symptoms of CG patients has not attracted enough attention. This study aimed to identify the associations between different symptoms and dietary factors. Patients and Methods. All CG patients in this cross-sectional study were recruited from 3 hospitals in Beijing, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
(34 reference statements)
1
16
1
4
Order By: Relevance
“…Chronic gastritis refers to chronic inflammatory lesions of gastric mucosa caused by various factors. Chronic gastritis can be diagnosed by gastroscopy, and its incidence ranks first among various stomach diseases [2]. Gastric ulcer is an ulcer caused by the damage of the mucosal muscle layer caused by gastric acid digestion of gastrointestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic gastritis refers to chronic inflammatory lesions of gastric mucosa caused by various factors. Chronic gastritis can be diagnosed by gastroscopy, and its incidence ranks first among various stomach diseases [2]. Gastric ulcer is an ulcer caused by the damage of the mucosal muscle layer caused by gastric acid digestion of gastrointestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ingestion of fried foods, barbecued foods, snacks, and very sweet, spicy, and salty foods from Western dietary patterns may activate innate immunity by producing excessive amounts of pro-inflammatory cytokines, resulting in chronic systemic or tissuespecific simmering inflammation in the stomach, gastric distension, and chronic or frequent stomach aches [59]. In patients with chronic gastritis, gastrointestinal symptoms were correlated with unhealthy dietary factors and food preferences, among which irregular mealtimes and consumption of salty and sweet foods were found to be the strongest risk factors [25]. From these studies, it is evident that dietary and lifestyle habits influence the risk of the progression of precancerous gastric lesions, leading to disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that diet plays an important role in the etiology of chronic inflammation of the gastric mucosa [22][23][24][25][26][27][28][29][30][31]. A high-fat diet impairs the gastrointestinal tract by producing bile acids, resulting in the expression of pro-inflammatory enzymes and cytokines that contribute to the development of insulin resistance [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food preferences are determinants of food choices [ 7 ] and are also significantly associated with the followed diet [ 8 ] and its health-related consequences, including body mass [ 9 ], obesity risk [ 10 ], and gastrointestinal symptoms [ 11 ]. As a result, understanding food preferences is necessary for public health purposes, to enable adequate nutritional education to improve the general quality of diet and influence food choices [ 12 ].…”
Section: Introductionmentioning
confidence: 99%